Developing sustainable research careers for KL2 scholars: The importance of an inclusive environment and mentorship. Issue 4 (31st August 2017) - Byington, Carrie L.; Rothwell, Erin; Matheson, Trent; Childs, Rebecca; Wachs, Erin; Rocha, Ruben; Murtaugh, Maureen; Turok, David; Letsou, Anthea; Shakib, Julie; Hess, Rachel; Dere, Willard
Abstract : Introduction: The National Clinical and Translational Science Award (CTSA) Consortium 2.0 has developed common metrics as a collaborative project for all participating sites. Metrics address several important aspects and functions of the consortium, including workforce development. The first workforce development metrics to be proposed for all CTSA hubs include the proportion of CTSA-supported trainees and scholars with sustainable careers in translational research and the diversity and inclusiveness of programs. Methods and results: The University of Utah Center for Clinical and Translational Science (CCTS), a CTSA hub, has been actively engaged in mentoring translational scientists for the last decade. We have developed programs, processes, and institutional policies that support translational scientists, which have resulted in 100% of our KL2 scholars remaining engaged in translational science and in increasing the inclusion of individuals under-represented in medicine in our research enterprise. In this paper, we share details of our program and what we believe are evidence-based best practices for developing sustainable translational research careers for all aspiring junior faculty members. Conclusions: The University of Utah Center for Clinical and Translational Science has been integral in catalyzing interactions across the campus to reverse the negative trends seen nationally in sustaining clinician scientists. Our programs and processes can serve as a model for other institutions seeking to develop translational scientists.